The Justinianic Plague: an interdisciplinary review. (October 2019) - Eisenberg, Merle; Mordechai, Lee
Abstract : This article is a detailed critical review of all the major scholarly publications in the rapidly expanding field of the Justinianic Plague published from 2000 through 2018. It updates the article in this journal by Dionysios Stathakopoulos from 2000, while also providing a detailed appraisal of the state of the field across all disciplines, including: literary studies, archaeology, DNA evidence, climatology, and epidemiology. We also identify the current paradigm for the Justinianic Plague as well as survey possible avenues forward for the field in the future. 1